THE INFLUENCE OF RENAISSANCE HUMANISM IN CHRISTOPHER MARLOWE’S POETRY (International Journal of Food and Nutritional Sciences, 2022)
This paper explores the profound influence of Renaissance humanism on the poetry of Christopher Marlowe, a key figure in Elizabethan literature. Renaissance humanism, a philosophical movement that emerged during the 14th to 17th centuries, emphasized the value of the individual, the potential of human reason, and the rediscovery of classical antiquity. Marlowe’s works reflect these humanist ideals, often portraying characters driven by ambition, intellectual curiosity, and the pursuit of personal greatness, while also engaging with the tensions between individual desires and societal or divine constraints. The paper argues that Marlowe’s poetry, particularly Hero and Leander, exemplifies Renaissance humanism in its emphasis on the individual's pursuit of knowledge and love, as well as its exploration of human limitations. By drawing on classical myth and philosophy, Marlowe reflects a humanist celebration of human potential, while simultaneously highlighting the vulnerability and fragility inherent in human experience. The paper also examines how Marlowe’s use of classical forms, including blank verse and rhymed couplets, mirrors the humanist revival of ancient literary traditions, showcasing his mastery of language and rhetorical style.